The Discourse of Hijab and Moral Standards of Muslim Women from the Perspective of Instagram Netizens - Irsani Kasim; Aswan Aswan (Citra Media Publishing, 2026)
This study discusses Hijab and Netizen Perspective Morals (Discourse Analysis of the Nissa Sabyan Case on Instagram Gossip @lambe_turah). This study aims to: find out the discourse on hijab and morality from the perspective of netizens in the case of Nissa Sabyan on Instagram Gossip @lambe_turah; and find out about the social practice of hijab and morality on netizen accounts in the case of Nissa Sabyan on Instagram Gossip @lambe_turah. This type of research is descriptive qualitative research with Norman Fairclough’s discourse analysis approach. The research data were obtained through documentation of netizen comments on the gossip Instagram account @lambe_turah and through literature studies to support the research. The results of the study show that the hijab is an identity of a Muslim woman, and this identity is often expressed through the religious aspect of appearance. In the view of the community, the hijab is always identified with good behaviour, so that hijab users are required always to look good and cannot be wrong in society. The social practice of netizens in providing comments is influenced by the discourse that develops in society, which holds that a person who wears a hijab must also have good behaviour. Netizens who provide comments use personal accounts that are not associated with any institution.